Effective Use Of Information Communication Technologies In Schools - Kamaladin Kuronboyevich Matyakubov (Euro Asian Journal Publishing, 2024)
This article introduces information and communication technologies in the field of education, their practical application and thus ensure the effectiveness of education. is calculated
Keywords: information communication technologies; efficiency; use; school